2015
DOI: 10.1021/acs.iecr.5b01459
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and Morphologies of Droplet Coalescence

Abstract: By the combination of high-speed imaging and numerical simulation, we explore the hydrodynamics and possible morphologies of the entire coalescence of a pendent droplet and sessile one. We identify three types of coalescence morphologies and plot a corresponding phase diagram to identify them depending on the Bond number and the size ratio between the two droplets. In addition to the well-known linear inertial growth of the liquid bridge at the initial contact of the two drops, we observe a new subsequent slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…It should be noted that the large contact angle of superhydrophobic surfaces allows us to explore the long term growth of the liquid bridge. Chen et al 41 investigate the coalescence of a pendent droplet with a sessile droplet and find that the prefactor in region II is 0.87. 9 The follow prefactors in region I for water are measured by other researchers: 1.09, 7 1.14, 8 1.10.…”
Section: Transition Of Interface Curvature During the Liquid Bridge Gmentioning
confidence: 99%
“…It should be noted that the large contact angle of superhydrophobic surfaces allows us to explore the long term growth of the liquid bridge. Chen et al 41 investigate the coalescence of a pendent droplet with a sessile droplet and find that the prefactor in region II is 0.87. 9 The follow prefactors in region I for water are measured by other researchers: 1.09, 7 1.14, 8 1.10.…”
Section: Transition Of Interface Curvature During the Liquid Bridge Gmentioning
confidence: 99%
“…system by 21-76 ∘ C compared with that of the CE resin. 12 Additionally, phosphorus-containing hybridized multiwalled carbon nanotubes (PMWCNTs) lowered the curing temperature of PMWCNT/CE composites by 45-71 ∘ C. 13 Poly(silylene-arylacetylene) (PSA) resin is a highly heat-resistant hybrid polymer with -Si-C≡C-Ar-C≡C-units. The cyclotrimerization and Diels-Alder addition of PSA resin forms benzene and naphthalene structures in the crosslinked network by thermal self-polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several attempts have also investigated the flow characteristics of liquid bridge between droplets in the initial stage, and have demonstrated that the temporal evolution of liquid bridge radius ( R b ) is in line with the scaling law R b ∝ t 0.5 . Additionally, the entire coalescence process of a pendent droplet and sessile one can be distinguished into three types of coalescence morphologies, and there is another scaling law for the liquid bridge expansion besides the well‐known one in the whole process . Note that, for the droplet coalescence in the air, the effect of the air can be negligible.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Additionally, the entire coalescence process of a pendent droplet and sessile one can be distinguished into three types of coalescence morphologies, and there is another scaling law for the liquid bridge expansion besides the well-known one in the whole process. [23] Note that, for the droplet coalescence in the air, the effect of the air can be negligible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation